Detection of serum neutralising antibodies to the ibr/ipv. virus in dairy cattle - ΠΑΠΠΟΥΣ, X.; ΣΕΪΤΑΡΙΔΗΣ, Κ.; ΔΗΜΗΤΡΙΑΔΗΣ, Ι. A. (Journal of the Hellenic Veterinary Medical Society, 2019)
A serological survey made in 1021 dairy cattle on 75 herds from Attica and some other breeding showed that 16,8% of the examined animals had IBR/IPV virus neutralizing antibodies and 32% of these herds had one, more or all the animals positive. Animals from other regions or abroad were introduced in all but one herds with positive animals. 23 out of 32 from such herds, that is 71,9% had animal(s) with neutralizing antibodies. In 43 herds with no introduced animals only one out of 369 cattle had neutralizing antibodies and it seems that infection by IBR/IPV virus in such herds is rare.